The genera Tropidozineus Monné & Martins, 1976 and Ozineus Bates, 1863 in Bolivia (Coleoptera: Cerambycidae: Lamiinae): six new species and a new synonym - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2012)
New species in the genera Tropidozineus Monné & Martins, 1976 and Ozineus Bates, 1863 from Bolivia are described: Tropidozineus wappesi sp. nov., from Bolivia (Santa Cruz) and Brazil (Amazonas), Tropidozineus adustus sp. nov., Ozineus griseostigma sp. nov., O. achirae sp. nov., O. argus sp. nov., and O. caliginosus sp. nov., all from Bolivia (Santa Cruz). A new synonym is proposed: Ozineus dubius Aurivillius, 1922 = Ozineus cinerascens Bates, 1863. Keys to the species of Tropidozineus and Ozineus from Bolivia are presented.